(untitled) - Grönroos, Christian; Christian Grönroos (Christian Grönroos, 2015)
Written by a leading pioneer in the field, the revised and updated fourth edition of this successful text examines service management and management in service competition from the point of view of the service profit logic. It focuses on adopting service logic in the management of service firms as well as of product manufacturers which want to become service providers
Keywords: Service industries; Customer services